2021
DOI: 10.1186/s12967-020-02691-4
|View full text |Cite
|
Sign up to set email alerts
|

Model based on five tumour immune microenvironment-related genes for predicting hepatocellular carcinoma immunotherapy outcomes

Abstract: Background Although the tumour immune microenvironment is known to significantly influence immunotherapy outcomes, its association with changes in gene expression patterns in hepatocellular carcinoma (HCC) during immunotherapy and its effect on prognosis have not been clarified. Methods A total of 365 HCC samples from The Cancer Genome Atlas liver hepatocellular carcinoma (TCGA-LIHC) dataset were stratified into training datasets and verification d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 64 publications
2
31
0
Order By: Relevance
“…According to American Cancer Statistics 2021, there will be approximately 40,000 new cancer cases and 30,000 deaths per year, with a 5-year relative survival rate of only 20% [3]. HCC is a complex and multistage disease that may be explained by genetic and epigenetic changes [4][5][6][7][8]. Despite the development of surgery and combined treatment, as well as progress in early diagnosis and interventional therapy, most patients are still diagnosed in the advanced stage of HCC with a low 5-year survival rate and poor prognosis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to American Cancer Statistics 2021, there will be approximately 40,000 new cancer cases and 30,000 deaths per year, with a 5-year relative survival rate of only 20% [3]. HCC is a complex and multistage disease that may be explained by genetic and epigenetic changes [4][5][6][7][8]. Despite the development of surgery and combined treatment, as well as progress in early diagnosis and interventional therapy, most patients are still diagnosed in the advanced stage of HCC with a low 5-year survival rate and poor prognosis [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the survival prediction of patients with prognostic biomarkers, individualized treatment can be better developed in clinical practice (15,16). Compared with a single gene, a multigenebased model has been shown to be more robust and precise in diagnosis and prognosis in many cancers (17,18). Thus, it provides new options for prognostic prediction and treatment of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, however, although the differences in the above-mentioned clinical trial data were reported to be statistically significant, this gene signature does not adequately distinguish between responders and nonresponders. Recently, a five-gene immune-related signature ( LDHA , PPAT , BFSP1 , NR0B1 , and PFKFB4 ) was identified and used to establish a prognostic model for responses to HCC treatment that could stratify patients who were sensitive to immunotherapy ( 93 ). Other studies using different gene combination strategies have also reported their potential to predict ICI responses by reflecting the characteristics of the immune microenvironment ( 94 , 95 ).…”
Section: Potential Predictive Biomarkers For Ici-based Treatmentmentioning
confidence: 99%